(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The updating of the Cuban economic model has brought the local development term back to debate, its validity and relevance have been reborn. The need for local development has gained strength from the battle waged to guarantee the updating of the Cuban socioeconomic model. Territorial development in Cuba unfolds in a context determined by excessive centralization, hindering a dynamic that allows local initiative. The decentralization process has suffered from a clear perspective in the conceptual order, an adequate regulatory framework and an explicit policy. Exposing viable alternatives for the sustenance of a good policy of local socio-economic development, through the application of legal norms, is the guiding thread of this work.